Crop rotation and a rye cover crop have minor impacts on soil health, microbial communities, and soybean yield in Ohio - Frey, Timothy S.; Shah, Denis A.; Lindsey, Laura E.; Sprunger, Christine; Lopez-Nicora, Horacio D.; Benitez Ponce, M. Soledad (Frontiers in Soil Science, 2025)
Crop rotations in the Midwest U.S. have become less diversified over the last twenty years while at the same time cover crop acreage has increased. The impact of these changes on soil health and soil microbial communities is not entirely understood. In rotational plots at two sites in Ohio, we investigated the impact of a corn-soy-wheat crop rotation and a rye cover crop on soil carbon, nitrogen, soil organic matter, and their relationships with soybean yield. Rhizosphere fungal, arbuscular mycorrhizal fungal, and bacterial communities were also assessed, as well as soil health and yield parameters. Microbial communities were measured using long and short-read amplicon sequencing on the PacBio and Illumina platforms. Small changes in soil health parameters were observed, including increased soil protein in the cover crop treatment at one of the sites. We also observed increasing yields in the diversified rotations and cover crops at one site. Soil bacterial and fungal communities showed differences driven by site, and AM fungi showed differences by rotation in one site-year combination. Network analysis revealed several fungal network modules correlated with increases in POXC and bacterial network modules correlated with soil protein and respiration. This research uniquely addresses the interactions between cover crops and diversified rotations and their impact on soil health in no-till production in Ohio.